Repercusión psicosocial en pacientes con traumatismos de extremidades superiores e inferiores hospitalizados en el servicio de traumatología del Hospital General IEES Babahoyo, mayo - agosto de 2024. - Llanos Yánez, Luis Alfredo (2024)
The research focuses on the psychosocial impact of grade III trauma to the upper and lower extremities, a significant problem that affects the quality of life of patients and represents a challenge in the field of public health. The general objective of the study is to determine the psychosocial repercussions in patients hospitalized in the traumatology service of the IEES Babahoyo General Hospital during the period from May to August 2024. A mixed methodology (qualitative - quantitative) was used, using a structured questionnaire of 16 questions that was applied to 30 patients, in order to collect data on their emotional and social status. In this research project, the results obtained reveal that a large part of the patients present symptoms of anxiety, depression and low self-esteem, which indicates a deterioration in their emotional well-being. In addition, the limitation in the ability to walk has had a negative impact on their social, work and academic life, generating frustration and a feeling of dependence. The general perception of health among these patients is negative, which has led to greater contact between nursing staff and caregivers with them, highlighting the need for more comprehensive care. In this way, it has been concluded that it is important to address both the physical and emotional aspects in the recovery process of these patients, in order to facilitate their social reintegration.